Trade in substandard and falsified medicines - Hagen, N; Hauk, C; Heide, L (Nomos, 2022)
According to WHO, 10.5% of medicines in low- and middle-income countries are substandard or falsified (SF), which has a multidimensional impact on public health as well as severe economic and socioeconomic consequences. Constrained access, weak technical capacity and poor governance contribute to the emergence of SF medicines. The increasing complexity of supply chains in our globalised world and the growing popularity of e-commerce provide numerous entry points for illegal medical products in both the Global South and the Global North. The COVID-19 pandemic led to a global surge in SF medicines. Various actors are involved in the trafficking of SF medicines. Key elements to combat SF medicines are prevention, detection and response with united, global participation of all parties involved.